2017
DOI: 10.1016/j.hoc.2016.08.006
|View full text |Cite
|
Sign up to set email alerts
|

Lung Cancer Biomarkers

Abstract: Synopsis The molecular characterization of lung cancer has considerably changed the classification and treatment of these tumors, becoming an essential component of pathologic diagnosis and oncologic therapy decisions. Through the recognition of novel biomarkers, such as epidermal growth factor receptor mutations and anaplastic lymphoma kinase translocations, it has been possible to identify subsets of patients who benefit from targeted molecular therapies. The success of targeted anticancer therapies and new … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
186
1
14

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 211 publications
(201 citation statements)
references
References 94 publications
(168 reference statements)
0
186
1
14
Order By: Relevance
“…Among them, LAC is the most common pathological type, and it has gradually increased in recent years [1]. Studies have shown that some gene mutations and protein expression abnormalities are closely related to the occurrence and development of LAC, and some molecular targeted drugs have been used in clinical practice [3,18,19]. STIP1 is a is an adaptor protein that combines heat shock protein 70 and heat shock protein 90 to modulate biological effects such as transcription, translation, and protein folding, and promotes the growth of tumor cells [12,20,21].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among them, LAC is the most common pathological type, and it has gradually increased in recent years [1]. Studies have shown that some gene mutations and protein expression abnormalities are closely related to the occurrence and development of LAC, and some molecular targeted drugs have been used in clinical practice [3,18,19]. STIP1 is a is an adaptor protein that combines heat shock protein 70 and heat shock protein 90 to modulate biological effects such as transcription, translation, and protein folding, and promotes the growth of tumor cells [12,20,21].…”
Section: Discussionmentioning
confidence: 99%
“…Structural changes (mutation, overexpression or rearrangement) of these specific oncogenes can trigger and promote the development of LAC cells [3][4][5]. So far, it has been known that lung cancer patients associated with driving genetic mutations have reached 62% of the total number of lung cancers [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…11 Primary lung cancer is the most common malignancy after non-melanocytic skin cancer, and the leading cause of human cancer deaths worldwide, with an overall 5-year survival rate of 10% to 15%. 12,13 Nonsmall-cell lung cancer (NSCLC) accounts for 80-85% of lung cancers, it is subdivided into three distinct histological subtypes: adenocarcinoma, lung squamous cell carcinoma (SQCC) and large cell carcinoma. 14, 15 Studies have shown that smoking is the main risk factor of lung cancer, accountable for 80% of cases.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have identified multiple gene expression subtypes that differ in prognosis, genomic alterations, clinical characteristics, including tumor differentiation, stage-specific survival, underlying drivers, and potential responses to treatment within LUAD and SCLC (Wilkerson et al, 2010;Thomas et al, 2014;Lu et al, 2016). For example, LUAD patients that harbor EGFR, ALK, ROS1, or BRAF mutations were discovered to benefit the most (Villalobos and Wistuba, 2017;Herbst et al, 2018). Targeted therapies for gene abnormalities of HER2, MET, RET, and NTRK1 appear to be an effective approach to treat LUAD (Dearden et al, 2013;Mazieres et al, 2013).…”
Section: Introductionmentioning
confidence: 99%